The Influence of Economic Uncertainty on Food Security and the Moderating Role of Trade Openness in Developing Countries - Algifahri, Astria; Heriqbaldi, Unggul (Universitas Airlangga, 2023)
This research examined the influence of economic uncertainty and the moderating role of trade openness on food security in 58 developing countries from 2012 to 2021. The dynamic panel data from the two-step System GMM was utilized to accomplish this. The findings of this research revealed that economic uncertainty did not exert a significant influence on food security in developing countries. Conversely, trade openness demonstrated a positive and significant effect in enhancing food security. Trade openness strengthened the adverse influence of economic uncertainty on food security in developing countries. The estimation results show trade openness has a significant positive effect of 0.0518, economic uncertainty has a positive but insignificant effect on food security, and Economic uncertainty when moderated by trade openness, shows a significant negative effect of -0.0533. The findings indicate that economic uncertainty does not significantly affect food security in developing countries. However, trade openness positively and significantly influences food security, suggesting that increased trade openness can enhance a country's food security. The results reveal a significant negative effect when considering both trade openness and economic uncertainty. It implies that implementing policies that reduce trade openness can enhance food security in high economic uncertainty.